Wirtualizacja jako strategia rozwoju przedsiębiorstw w warunkach integracji i globalizacji - Kisielnicki, Jerzy (The Virtualization as a Strategy of Development of Enterprises in Conditions of Integration and Globalization, 2006)
The hypothesis in the article represents, that thanks to virtualization process of transformation of the enterprise (particularly small the and averages) the strategy development could be accepted. Thereupon they will become competitive in conditions of globalization. Virtualization allow individual enterprises, on ingress in strategic cooperative alliance from different similar enterprises. The presented study was concentrated on following theoretical and practical problems: the analysis of the virtualization as a new trend in business cooperation, strategic analysis of strong, weak sides as well as chances and threats of these enterprises which has accepted the new strategy and owing to this, they can function on the global market, as well as the analysis of the cases.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1116, s. 280-290